Analisis Aksesibilitas Menuju Lokasi Kawasan Pariwisata di Provinsi Bali dengan Indeks Hansen dan Statistik Deskriptif - Indrashwara, Decky Cipta; Surya Tapa, I Gede Fery; Kumara, I Nyoman Indra; Ratih Suwarningsih, Ketut Ayu (Jurnal Ilmiah Poli Rekayasa, 2024)
Bali is one of the provinces in Indonesia which has excellence in tourism. The distribution and development of tourism activities in Bali are considered to be less evenly distributed. In certain areas, there is a development of activities that exceed needs, while in other areas there is a shortage of activities. One way to measure the distribution of tourism activities in the Province of Bali is based on accessibility. In this study, the analysis of accessibility toward tourism area location is conducted with the resistance factor of mileage and traveling time using Bali as the case study. Accessibility is a comfort measure or eases the achievement of land use through the transportation network system. This study aims to analyze the accessibilities and their distributions using the mileage and traveling time and to provide alternative solutions to increase accessibility in the least visited area in Bali Province. Accessibility is calculated using Hansen’s index and descriptive statistics. Having calculated the mileage and traveling time, these values are used as Z-Score. Using this Z-Score, the distribution of accessibility based on mileage and traveling time can be analyzed. The results indicate that the highest level of accessibility based on the mileage and traveling time is in Denpasar city. On the other hand,  the lowest accessibilities according to the mileage and traveling time are found in Jembrana, Tabanan, Buleleng, and Karangasem regencies. The distribution of tourist area accessibility can be seen in the Z-Score. This score indicates that the district with low accessibility based on the mileage and traveling time is in Jembrana, Tabanan, Buleleng, and Karangasem regencies. Alternatively, several solutions can be done to increase the accessibility at the least visited area in Bali province such as road widening, building toll road construction, multiplying the construction of shortcut, and railroad development.